Nitrated Fatty-Acids Distribution in Storage Biomolecules during Arabidopsis thaliana Development - Lorena Aranda-Caño; Raquel Valderrama; Mounira Chaki; Juan C. Begara-Morales; Manuel Melguizo; Juan B. Barroso (Antioxidants, 2022)
The non-enzymatic interaction of polyunsaturated fatty acids with nitric oxide (NO) and derived species results in the formation of nitrated fatty acids (NO2-FAs). These signaling molecules can release NO, reversibly esterify with complex lipids, and modulate protein function through the post-translational modification called nitroalkylation. To date, NO2-FAs act as signaling molecules during plant development in plant systems and are involved in defense responses against abiotic stress conditions. In this work, the previously unknown storage biomolecules of NO2-FAs in Arabidopsis thaliana were identified. In addition, the distribution of NO2-FAs in storage biomolecules during plant development was determined, with phytosterol esters (SE) and TAGs being reservoir biomolecules in seeds, which were replaced by phospholipids and proteins in the vegetative, generative, and senescence stages. The detected esterified NO2-FAs were nitro-linolenic acid (NO2-Ln), nitro-oleic acid (NO2-OA), and nitro-linoleic acid (NO2-LA). The last two were detected for the first time in Arabidopsis. The levels of the three NO2-FAs that were esterified in both lipid and protein storage biomolecules showed a decreasing pattern throughout Arabidopsis development. Esterification of NO2-FAs in phospholipids and proteins highlights their involvement in both biomembrane dynamics and signaling processes, respectively, during Arabidopsis plant development.